APPLICATION OF UNMANNED AERIAL VEHICLE AS A BASE MAP LAYER IN NEAR-SURFACE GEOPHYSICS - Muhammad Yanis; Aprilla Hasibuan Anggini; Faisal Abdullah; Muzakir Zainal; Marwan Abubakar (Universitas Negeri Medan, 2021)
The Geophysical method is operated by using physical parameters above the surface to estimate the subsurface structures. In data interpretation, all 3D surveys, i.e., magnetic, gravity, magnetotelluric, and airborne, are required for geographical conditions in the research area. In a large area, global DEM data is used to explain the field condition, but for local measurement, the data is not efficient due to low resolution (15-30 m/px). This research uses UAV technology to produce a high-resolution topography in local Geophysical measurement (500 x 600 m). The survey was conducted to map the coal structure in the subsurface. UAV data were also compared to SRTM (30 m/px) and DEMNAS (8 m/px) as global topography. Based on data processing, the UAV topographic was have a high resolution of 2.5 cm/px. Comparison of UAV and magnetic data are able to explain a good condition of field measurement than a global DEM data, even in a relatively small area; outcrops of the coal (50x50 m) can show a good differences contrast of topography. Based on data analysis, we can conclude that UAV technology can interpret the geophysical data measured in a local area.Keywords: UAV, SRTM, Topography, Geophysical Interpretation.Metode Geofisika bekerja dengan memanfaatkan parameter fisis diatas permukaan untuk pendugaan struktur bawah permukaan. Dalam tahapan interpretasi data, semua pengukuran 3D Geofisika; magnetic, gravity, magnetotelluric, dan airbone sangat membutuhkan keadaan geografis lapangan. Pada area yang luas, data DEM global digunakan untuk menjelaskan deskripsi lapangan, namun untuk pengukuran dekat permukaan yang bersifat lokal, data ini tidaklah efesien, karena resolusi yang relative rendah (15 – 30 m/px). Kami menggunakan teknologi UAV untuk menghasilkan topografi resolusi tinggi pada area pengukuran Geofisika dengan luas 500 x 600 m, yang disurvei untuk pemetaan batubara dibawah permukaan. Data UAV juga dibandingkan dengan topografi global SRTM (30 m/px) dan DEMNAS (8 m/px). Hasil pengolahan data menunjukkan data UAV menghasilkan topografi dengan resolusi 2.5 cm/px. Hasil overlay UAV dengan Geofisika magnetik mampu menjelaskan deskripsi lapangan dengan sangat baik dibandingkan DEM global, bahkan pada area yang relative kecil seperti singkapan batuabara (50x50 m) dapat menunjukkan keadaan perbedaan topografi dengan kontras. Berdasarkan data analysis, topografi UAV sangat potensial digunakan untuk interpretasi data Geofisika dekat permukaan yang diukur pada area yang relative lokal.Kata kunci: UAV, SRTM, Topografi, Interpretasi Geofisika.